A model for microbial phosphorus cycling in bioturbated marine sediments: Significance for phosphorus burial in the early Paleozoic. (15th September 2016) - Dale, Andrew W.; Boyle, Richard A.; Lenton, Timothy M.; Ingall, Ellery D.; Wallmann, Klaus
Highlights: An empirical diagenetic model includes redox-dependent P storage by microorganisms. Sediment mixing and burrowing by animals strongly enhances P burial. Supporting evidence for a decrease in oceanic P inventory in the early Paleozoic. Abstract: A diagenetic model is used to simulate the diagenesis and burial of particulate organic carbon (Corg ) and phosphorus (P) in marine sediments underlying anoxic versus oxic bottom waters. The latter are physically mixed by animals moving through the surface sediment (bioturbation) and ventilated by burrowing, tube-dwelling organisms (bioirrigation). The model is constrained using an empirical database including burial ratios of Corg with respect to organic P (Corg :Porg ) and total reactive P (Corg :Preac ), burial efficiencies of Corg and Porg, and inorganic carbon-to-phosphorus regeneration ratios. If Porg is preferentially mineralized relative to Corg during aerobic respiration, as many previous studies suggest, then the simulated Porg pool is found to be completely depleted. A modified model that incorporates the redox-dependent microbial synthesis of polyphosphates and Porg (termed the microbial P pump) allows preferential mineralization of the bulk Porg pool relative to Corg during both aerobic and anaerobic respiration and is consistent with the database. Results with this model show that P burial is strongly enhanced in sediments hosting fauna. Animals mix highly labile Porg away from the aerobic sediment layers where mineralization rates are highest, thereby mitigating diffusive PO4 3− fluxes to the bottom water. They also expand the redox niche where microbial P uptake occurs. The model was applied to a hypothetical shelf setting in the early Paleozoic; a time of the first radiation of benthic fauna. Results show that even shallow bioturbation at that time may have had a significant impact on P burial. Our model provides support for a recent study that proposed that faunal radiation in ocean sediments led to enhanced P burial and, possibly, a stabilization of atmospheric O2 levels. The results also help to explain Corg :Porg ratios in the geological record and the persistence of Porg in ancient marine sediments.